(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The notion of reflextion has been more exact: components, criteria, exponents and levels have been illuminated as components of a model’s structure of pedagogical university student’s reflextion forming in the process of self-dependent learning activity.